Spectral optical properties of soot: laboratory investigation of propane flame particles and their link to composition - J. Heuser; C. Di Biagio; J. Yon; M. Cazaunau; A. Bergé; A. Bergé; E. Pangui; M. Zanatta; M. Zanatta; L. Renzi; A. Marinoni; S. Inomata; et al. (Atmospheric Chemistry and Physics, 2025)
Soot aerosol generated from the incomplete combustion of biomass and fossil fuels is a major light-absorber; however its spectral optical properties for varying black carbon (BC) and brown carbon (BrC) content remain uncertain. In this study, soot aerosols with varying maturity and composition, i.e. elemental-to-total-carbon ratio (EC/TC<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="38pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="a434d3ed47844dbe9a7417ac781bab9e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6407-2025-ie00001.svg" width="38pt" height="14pt" src="acp-25-6407-2025-ie00001.png"/></svg:svg>), have been studied systematically in a large simulation chamber to determine their mass absorption, scattering, and extinction cross sections (MAC, MSC, MEC); single-scattering albedo (SSA); and absorption and scattering Ångström exponents (AAE, SAE). The MAC, MEC, SSA, and AAE show a variability between the different types of soot with varying EC/TC<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="38pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="d98c3dd06629c9ce353405ed57451d0d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6407-2025-ie00002.svg" width="38pt" height="14pt" src="acp-25-6407-2025-ie00002.png"/></svg:svg> ratios. The MAC (MEC) at 550 nm increases for increasing EC/TC<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="38pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="7c7ca3abf63eb567996671d1b7f250c0"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6407-2025-ie00003.svg" width="38pt" height="14pt" src="acp-25-6407-2025-ie00003.png"/></svg:svg>, with values of 1.0 (1.4) m2 g−1 for EC/TC<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="38pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="54ffed50687805c6f186d5877b6bdd3b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6407-2025-ie00004.svg" width="38pt" height="14pt" src="acp-25-6407-2025-ie00004.png"/></svg:svg> = 0.0 (BrC-dominated soot) and 4.6 (5.1) m2 g−1 for EC/TC<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="38pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="16b788defa5a132fb643f6a1bb090717"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6407-2025-ie00005.svg" width="38pt" height="14pt" src="acp-25-6407-2025-ie00005.png"/></svg:svg> = 0.79 (BC-dominated soot). The AAE and SSA (550 nm) decrease from 3.79 and 0.29 (EC/TC<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="38pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="0f8b86a481edcacac1ef37cd868a5b8b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6407-2025-ie00006.svg" width="38pt" height="14pt" src="acp-25-6407-2025-ie00006.png"/></svg:svg> = 0.0) to 1.27 and 0.10 (EC/TC<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="38pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="1c460d6c2eab28f7193cb4f3294a7110"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6407-2025-ie00007.svg" width="38pt" height="14pt" src="acp-25-6407-2025-ie00007.png"/></svg:svg> = 0.79). Combining present results for soot from propane combustion with literature data for flame soot from diverse fuels supports a generalised exponential relationship between particle EC/TC<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="38pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="e5fb6256d98cd87c1d78541e399c7371"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6407-2025-ie00008.svg" width="38pt" height="14pt" src="acp-25-6407-2025-ie00008.png"/></svg:svg> and its MAC and AAE values (MAC550=(1.3±0.05)<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="111pt" height="13pt" class="svg-formula" dspmath="mathimg" md5hash="cdb2fc036bea96fec148c35e0bf563a1"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6407-2025-ie00009.svg" width="111pt" height="13pt" src="acp-25-6407-2025-ie00009.png"/></svg:svg> e(1.8±0.1)<mfenced open="(" close=")">ECTC</mfenced><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="60pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="a6a8d7c905cd62cf94a92612e92feafb"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6407-2025-ie00010.svg" width="60pt" height="15pt" src="acp-25-6407-2025-ie00010.png"/></svg:svg>; AAE=(0.73±0.12)+(3.29±0.12)<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="170pt" height="12pt" class="svg-formula" dspmath="mathimg" md5hash="d4034e21b8206d1c809b37bf1ce1fe19"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6407-2025-ie00011.svg" width="170pt" height="12pt" src="acp-25-6407-2025-ie00011.png"/></svg:svg> e-(2.32±0.30)<mfenced open="(" close=")">ECTC</mfenced>)<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="78pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="4366cdc51fd2f29d7953dfc106a43db3"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-6407-2025-ie00012.svg" width="78pt" height="17pt" src="acp-25-6407-2025-ie00012.png"/></svg:svg>, which represents the optical continuum of spectral absorption for soot with varying maturity. From this, it is possible to extrapolate a MAC of 7.9 and 1.3 m2 g−1 (550 nm) and an AAE (375–870 nm) of 1.05 and 4.02 for pure EC (BC-like) and pure OC (BrC-like) soot. The established relationship can provide a useful parameterisation for models to estimate the absorption from combustion aerosols and their BC and BrC contributions.